A Modified Switching Regression Model for Earnings Differentials Between the Public and Private Sectors in the Netherlands - van Ophem, Hans (The Review of Economics and Statistics, 1993)
Hans van Ophem, A Modified Switching Regression Model for Earnings Differentials Between the Public and Private Sectors in the Netherlands, The Review of Economics and Statistics, Vol. 75, No. 2 (May, 1993), pp. 215-224